CASE REPORT: INNOVATIVE TREATMENT OF CUTANEOUS LARVA MIGRANS MANAGEMENT - Sukmawati Tansil Tan; Yohanes Firmansyah; Yurike Indah Pratiwi (Jurnal Medika Hutama, 2021)
Cutaneous larva migrans (CLM) is a skin infection caused by nematode larvae that penetrate actively and migrate within the epidermis of the skin. Several reports from the livestock sector report that resistance mechanisms are emerging due to the irrational use of anti-helminths. This case report describes a case of CLM that was treated with a new approach of using 5% permethrin cream topically for ten days (empirical therapy generally consists of Albendazole and Ivermectin with high resistance rates in animals). The 5% permethrin cream treatment effectively treats "creeping eruptions" with very itchy lesions on the dorsum palmar dextra with a tunnel-shaped appearance of hyperemic serpiginous papules. The patient admitted that he was delighted with the treatment without any side effects